2008
DOI: 10.1111/j.1360-0443.2008.02268.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived safety and efficacy of nicotine replacement therapies among US smokers and ex‐smokers: relationship with use and compliance

Abstract: The findings suggest that many smokers are misinformed about the health risks of NRT and that these misperceptions impede not only the adoption of NRT but also compliance during treatment. Misperception of NRT safety is one barrier to effective use of NRT and probably reduces success in quitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 22 publications
12
115
2
1
Order By: Relevance
“…36 The reasons that underlie the variations in the use of medications for tobacco cessation for patients who are older with more comorbidities are unclear, but may reflect safety concerns and fatalism on the part of patients and physicians. Though multiple studies have indicated that these therapies are safe to use in patients with a variety of medical conditions, 37,38 many patients have erroneous beliefs that nicotine replacement is dangerous or ineffective, 39,40 and these beliefs may be more common among patients who are older and sicker. Physicians and patients who are faced with continued tobacco use by a patient of advanced age or with significant medical comorbidity may feel fatalistic about the success and benefits of quitting.…”
Section: Discussionmentioning
confidence: 99%
“…36 The reasons that underlie the variations in the use of medications for tobacco cessation for patients who are older with more comorbidities are unclear, but may reflect safety concerns and fatalism on the part of patients and physicians. Though multiple studies have indicated that these therapies are safe to use in patients with a variety of medical conditions, 37,38 many patients have erroneous beliefs that nicotine replacement is dangerous or ineffective, 39,40 and these beliefs may be more common among patients who are older and sicker. Physicians and patients who are faced with continued tobacco use by a patient of advanced age or with significant medical comorbidity may feel fatalistic about the success and benefits of quitting.…”
Section: Discussionmentioning
confidence: 99%
“…Consecuentemente, sus hallazgos generan inquietud frente a la variabilidad en la población incluida en los ensayos clínicos, en donde la presencia de fumadores crónicos o con alta dependencia no ha sido suficientemente clara. Además, se ha revisado el escaso cumplimiento de las indicaciones terapéuticas, que sugieren el uso de reemplazo nicotínico por, al menos, seis semanas y la percepción equivocada sobre la magnitud del efecto para este tratamiento que lleva a desestimular a muchos de los fumadores por no encontrar alivio en corto tiempo o en la intensidad esperada (48)(49)(50).…”
Section: Discussionunclassified
“…At some point, the clinician advises the patient to quit and asks if she is willing to make a quit attempt. By now, she may well be in nicotine withdrawal because it has been hours since she last smoked; she still feels ill from the complaint that prompted the visit; and she knows little about what tobacco treatments are available [4], their efficacy [5] or what course of action her clinician thinks would be best for her.…”
Section: Response To Commentaries: Changing the Treatment Default Wilmentioning
confidence: 99%